URGENCY OF COMBINED ORAL CONTRACEPTIVES IN PROLONGED REGIMEN USE - A. L. Tikhomirov; A. A. Ledenkova (IRBIS LLC, 2016)
This article presents the issues on combined oral contraceptives use in prolonged regimen.